1984
DOI: 10.1001/archderm.120.5.631
|View full text |Cite
|
Sign up to set email alerts
|

Vitiligo treated with topical clobetasol propionate

Abstract: Seventy-five patients with vitiligo were treated with intermittent topical applications of clobetasol propionate for varying times within a three-year period. The best results occurred in the facial lesions of Asian or black patients. Repigmentation of 90% to 100% was achieved in more than 80% of patients with vitiligo of the face and more than 40% of patients with vitiligo on other parts of the body. Progressive repigmentation continued even after the treatment stopped. Intermittent therapy helped to avoid th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0
2

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 0 publications
2
42
0
2
Order By: Relevance
“…Considering the effectiveness of topical corticosteroids according to current data in vitiligo, betamethasone valerate cream as class III corticosteroid, was given to all patients. [192324]…”
Section: Discussionmentioning
confidence: 99%
“…Considering the effectiveness of topical corticosteroids according to current data in vitiligo, betamethasone valerate cream as class III corticosteroid, was given to all patients. [192324]…”
Section: Discussionmentioning
confidence: 99%
“…12 Higher response rates are seen in children compared to adults 2 ; head and neck lesions tend to have the greatest response to treatment. 2,3 In a review of 101 children treated with topical CSs alone, Kwinter et al 13 reported response rates of 64%. Complete repigmentation rates have been reported to be as high as 49.3%.…”
Section: Efficacy Of Topical Corticosteroidsmentioning
confidence: 99%
“…Topical corticosteroids have the best results (75% of repigmentation) on sun-exposed areas (face and neck), (82,83) in dark skin, (84) in recent lesions (85) and in children compared to adults (86) …”
Section: Topical Corticosteroidsmentioning
confidence: 99%